The Contribution of National Indigenous Organizations in Addressing the Missing and Murdered Indigenous Women and Girls (MMIWG) in Canada - Trianta Karana Putra (Pusat Studi Gender Universitas Jember, 2021)
The problem of missing and murdered indigenous women & girls (MMIWG) in Canada. This issue is one of the most pressing issues in Canada. MMIWG will be defined as a sociological phenomenon in which indigenous women's racial and gender identities characterize them as a marginalized group leading to increased violence, including a disproportionate rate at which indigenous women disappear and become victims of murder and sexual harassment. Using the concept of Non-Governmental Organizations (NGOs) and the concept of Human Rights Non-Governmental Organizations (HRNGOs), this study aims to determine the contribution of National Indigenous organizations in overcoming Missing and Murdered Indigenous Women and Girls (MMIWG) in Canada.